2021
DOI: 10.1002/deo2.5
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire survey on radiation protection among 282 medical staff from 26 endoscopy‐fluoroscopy departments in Japan

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Dosimeter wearing was extremely low among doctors (60%), unlike nurses (94%) and technologists (92%), which was similar to a previous report 9 and showed improvement by 8% from 52% of previous surveys but still is not enough (Figure S1). Similarly, surveys in other countries have reported low rates of doctors wearing dosimeters, and we believe that this is a common trend among doctors 6,12 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Dosimeter wearing was extremely low among doctors (60%), unlike nurses (94%) and technologists (92%), which was similar to a previous report 9 and showed improvement by 8% from 52% of previous surveys but still is not enough (Figure S1). Similarly, surveys in other countries have reported low rates of doctors wearing dosimeters, and we believe that this is a common trend among doctors 6,12 .…”
Section: Discussionsupporting
confidence: 86%
“…With this background, we conducted a survey on radiation protection for medical staff in endoscopy departments in Japan in 2020. This study revealed that staff did not have enough radiation protection equipment or education 9 . We speculate that this may be due to insufficient awareness‐raising activities by gastroenterology‐related societies in Japan.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Surprisingly, the wearing rate of endoscopists was reported to be 27% for a thyroid shield and 21% for lead glasses. 48 This indicates that gastroenterologists are regrettably still insufficiently aware of radiation protection. In addition, with the advent of the coronavirus disease 2019 (COVID-19), endoscopists are also required to wear face guards to protect against infection during procedures (Fig.…”
Section: Shieldingmentioning
confidence: 99%
“…However, many gastroenterologists do not routinely wear protective clothing during FGEP examinations. Surprisingly, the wearing rate of endoscopists was reported to be 27% for a thyroid shield and 21% for lead glasses 48 . This indicates that gastroenterologists are regrettably still insufficiently aware of radiation protection.…”
Section: Occupational Radiological Protection In Fgepsmentioning
confidence: 99%